Jerami Padi Fermentasi sebagai Alternatif Solusi Pakan Sapi Berkualitas di Desa Majasari, Indramayu - Ambarsari, Wiwik; Suherman, Asep; Mahmud, Yudhi (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2019)
The purpose of community service is to increase knowledge and skills to the community about fermentation of rice straw as an alternative to quality cow feed. This activity was held in May and August 1918 in the Cattle Groups Tunggal Rasa I and II, Majasari Village, Sliyeg District, Indramayu Regency. The method is carried out by lecturing and discussion, demonstration, and practice of making fermented rice straw with urea and bran. The result of this service is that cattle farmers have the knowledge and skills about fermentation of rice straw and cows like rice straw fermentation so that they can fulfill a quality alternative feed solution.